OPTIMIZATION OF PROTEASE FROM APERGILLUS NIGER IN SOLID STATE FERMENTATION FOR ENZYMATIC TREATMENT OF AQUACULTURE SLUDGE - OOI CHEE KUAN (UNIVERSITI MALAYSIA TERENGGANU, 2022)
Proteases or proteolytic enzymes, has high potential to be applied in wastewater treatment and improve sludge dewatering. Hence, the ultimate aim of this study is to produce and characterize protease from Aspergillus niger under solid-state fermentation (SSF) by utilizing shrimp shell powder as solid substrate. The produced protease was applied for enzymatic treatment to reduce organic matter and micropollutants in aquaculture sludge based on selected parameters. It was found that the produced protease from SSF was slightly alkaline. The correlation between factors operating parameters (incubation temperature, inoculum size, moisture content) for the production of enzyme are analysed using statistical software, Minitab 16. A 23 full factorial experimental design was employed and the enzyme produced was optimized by the method of desirability function. The optimal conditions for protease production of 3.7 U/mg were 35 °C of incubation temperature, 60% of initial moisture content and 1.0 of inoculum size.